Stand out with your scientific poster : A step by step approach - Verlinden, Toon, ....-; Van de Water, Hans, ....- (Gent : Academia Press, 2024)
Are you a researcher who struggles when it comes to creating scientific posters? Or do you simply want to get better at it? This book provides you with a step-by-step guide to making a poster that has real impact. To ensure you stand out from the crowd at your next poster fair.
Keywords: Presenteren